Test of The Effectiveness of Sweet Wood (Cinnamomum Burmanii) on Healing of Wood Wounds in Wistar Rats - Muhammad Chairul; Stevani Rose Br Sinaga; Boyke Marthin Simbolon (Eduvest - Journal of Universal Studies, 2025)
Incised wounds are disruptions of skin integrity that require effective treatment to accelerate healing. Cinnamon (Cinnamomum burmanii), rich in secondary metabolites such as eugenol, cinnamaldehyde, and flavonoids, is known for its potential as an anti- inflammatory, antioxidant, and antibacterial agent. This study aims to evaluate the effectiveness of cinnamon extract ointment in healing incised wounds in Wistar rats. This experimental study used a post-test only control group design. A total of 30 Wistar rats were divided into five groups: a negative control (ointment base), a positive control (gentamicin ointment), and three treatment groups with cinnamon extract ointments at concentrations of 10%, 20%, and 40%. Observations of wound length and healing percentages were conducted over 14 days. Data were analyzed using the Kruskal-Wallis and Mann-Whitney tests. The results showed a significant reduction in wound length in the 40% cinnamon extract ointment group (19.6 mm) compared to the negative control (12.8 mm) and were close to the effectiveness of gentamicin ointment (20 mm). The highest wound healing percentage was also achieved in the 40% concentration group (98.2%), comparable to gentamicin ointment (100%). Cinnamon extract ointment at a concentration of 40% effectively accelerates the healing of incised wounds in Wistar rats, with effectiveness comparable to gentamicin ointment. Further research is needed to evaluate its safety and clinical potential.